La materia orgánica particulada como indicador de cambios en la calidad de los suelos influenciados por los cambios de uso y la geología - Cueva Matailo, Yomaira Katerine (2022)
Particulate organic matter (MOP) is a dynamic component of the soil, which responds selectively and quickly to changes in management and different types of disturbances. The objective of this work was to quantify the MOP as an indicator of changes in the quality of the soils and to evaluate the potential of this variable as an indicator of their quality. To achieve this objective, soil samples were analyzed in the area of Chambo and Achupallas, in different land uses. The soil samples were separated through a 53 µm sieve, where the MOP associated with the fraction> 53 µm and the stabilized organic matter associated with the (MOE) associated with the F2 fraction ≤ 53 µm were obtained. In addition, the spectral signature of the MOP and MOE was determined using diffuse reflectance spectroscopy in Near Infrared (NIR) in the different land uses. The highest concentration of MOP is found in the soil under páramo with a carbon content of 212 g/kg and decreased to 61 g/ kg when it was replaced by cultivation. Diffuse reflectance (ERD) spectra were recorded in the range 350 nm to 2500 nm. On the other hand, the levels of MOP and MOE content were identified in the region of 600 to 920 nm in length. The MOP proved to be a good indicator to detect the changes that occur when natural vegetation is affected by the advance of the agricultural frontier.